2022
DOI: 10.3389/fendo.2022.901669
|View full text |Cite
|
Sign up to set email alerts
|

From an Empty Stomach to Anxiolysis: Molecular and Behavioral Assessment of Sex Differences in the Ghrelin Axis of Rats

Abstract: Ghrelin, a stomach-produced hormone, is well-recognized for its role in promoting feeding, controlling energy homeostasis, and glucoregulation. Ghrelin’s function to ensure survival extends beyond that: its release parallels that of corticosterone, and ghrelin administration and fasting have an anxiolytic and antidepressant effect. This clearly suggests a role in stress and anxiety. However, most studies of ghrelin’s effects on anxiety have been conducted exclusively on male rodents. Here, we hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Böchers et al recently confirmed that female rats have higher circulating ghrelin levels than males, and that ovariectomy resulted in reduced acyl-ghrelin concentrations using a well characterized acyl-ghrelin assay. These authors also and also showed that females have lower plasma concentrations of the liver anitimicrobial peptide-2 (LEAP-2), an endogenous antagonist to the GHSR (63,64).…”
Section: Ghrelin and Energy Balance In Females: Interaction With Ster...mentioning
confidence: 89%
See 1 more Smart Citation
“…Böchers et al recently confirmed that female rats have higher circulating ghrelin levels than males, and that ovariectomy resulted in reduced acyl-ghrelin concentrations using a well characterized acyl-ghrelin assay. These authors also and also showed that females have lower plasma concentrations of the liver anitimicrobial peptide-2 (LEAP-2), an endogenous antagonist to the GHSR (63,64).…”
Section: Ghrelin and Energy Balance In Females: Interaction With Ster...mentioning
confidence: 89%
“…Using quantitative polymerase chain reaction (qPCR), a recent study compared GHSR mRNA expression in the ARC and amygdala of male and female ad lib fed mice and mice that were fasted overnight. Female mice showed higher overall GHSR expression in both of these regions, especially in the amygdala (63). In another study, the issue of ghrelin sensitivity was examined indirectly by measuring Fos immunoreactivity (Fos-ir) in response to icv ghrelin infusions in female rats at different phases of the cycle.…”
Section: Ghsr Deletion + Ovariectomymentioning
confidence: 99%
“…Future research also should explore sex differences in passive avoidance behavior and the role of ghrelin signaling (and other interoceptive feedback signals) in that behavior, given our previous report that food deprivation suppresses conditioned passive avoidance in male, but not female, rats [7]. In this regard, recent evidence indicates that female rats have significantly higher plasma levels of acylghrelin compared to male rats under both fed and fasted conditions, and that females may be more sensitive to the anxiolytic effects of fasting-induced ghrelin signaling [25]. We reported that compared to male rats, female rats display markedly less conditioned passive avoidance behavior regardless of metabolic state at testing, consistent with other reports that female rodents show less passive and more active responses to threatening stimuli [7].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Food deprivation increases circulating levels of acyl-ghrelin [2325], and acyl-ghrelin reduces tonic firing and stimulus-induced responsiveness of vagal sensory neurons [26,27] and postsynaptic A2 neurons in the cNTS [28]. We recently demonstrated that systemic administration of a ghrelin receptor antagonist in fasted rats partially restores the ability of vagal sensory stimulation to activate PrRP+ A2 neurons and suppress food intake [20].…”
Section: Introductionmentioning
confidence: 99%
“…Whole brain irradiation in young rats have shown different impact on male and female [ 23 , 32 ]. Furthermore, animal behaviour in females is much more influenced by the sexual cycle [ 33 ]. To avoid the potential influence of sex hormone on the behavioural test, we used male rat pups only in this study.…”
Section: Methodsmentioning
confidence: 99%